2010
DOI: 10.1177/0363546510381362
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Positioning Analysis of Medial Patellofemoral Ligament Reconstruction

Abstract: The study highlights the difficulty of reproducible MPFL reconstruction. The surgical procedure continues to be improved and finding a reliable technique to anatomically place the graft remains challenging. Verifying femoral tunnel placement radiographically may be recommended during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
159
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(174 citation statements)
references
References 28 publications
8
159
1
6
Order By: Relevance
“…Within this sulcus, it should be noted that the MPFL has a broad femoral attachment similarly reported in other studies. 4,16,49 Knees with anatomic anomalies such as patella alta, trochlear dysplasia, quadriceps dysplasia, patellar tilt, and anterior tibial tubercle lateralization have a reported high association with symptomatic patellar instability when compared with control knees 11 and may also have altered ME and ATT anatomy as suggested by Servien et al 34 Recent studies 16,31 reported great anatomic variability of the ATT position assessed with computed tomography (CT) scans. Likewise, Sanchis-Alfonso et al 31 argued against the use of radiographic methods, as they do not account for anatomic variations in medial knee anatomy, particularly the ATT, thereby reflecting an added risk for malposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this sulcus, it should be noted that the MPFL has a broad femoral attachment similarly reported in other studies. 4,16,49 Knees with anatomic anomalies such as patella alta, trochlear dysplasia, quadriceps dysplasia, patellar tilt, and anterior tibial tubercle lateralization have a reported high association with symptomatic patellar instability when compared with control knees 11 and may also have altered ME and ATT anatomy as suggested by Servien et al 34 Recent studies 16,31 reported great anatomic variability of the ATT position assessed with computed tomography (CT) scans. Likewise, Sanchis-Alfonso et al 31 argued against the use of radiographic methods, as they do not account for anatomic variations in medial knee anatomy, particularly the ATT, thereby reflecting an added risk for malposition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the gross 4,19 and radiographic 50 anatomy of the medial knee has been well described, nonanatomic MPFL femoral tunnel placement is common, with proximal and anterior malposition typically reported. 7,27,34,46 Associated chronic anterior knee pain, iatrogenic medial patellar subluxation, recurrent lateral instability, increases in graft tension, medial patellar tilt, and medial patellofemoral contact pressures, as well as medial facet overload and resultant chondropathy, have been reported. 7,13,27,35,48 Likewise, nonanatomic MPFL reconstruction is a major risk factor for surgical failure, with a reported 67% of adolescent patients who develop recurrent patellar instability or patellofemoral arthrosis/pain having improper femoral tunnel position that was considered preventable.…”
mentioning
confidence: 99%
“…However, most patients exhibited habitual patellar dislocation with high-grade trochlear dysplasia, which could not correct the abnormal bone structure [9][10][11]. Patellar dislocation is often caused by a variety of abnormal anatomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies by Schöttle et al [22], the use of radioscopy is considered of great importance in determining the ideal anatomical point for graft fixation in the femur. Several authors have shown that nonanatomical positioning of the femoral tunnel interferes with the patellofemoral kinematics.…”
Section: Introductionmentioning
confidence: 99%